인산염계 부식억제제 주입이 배급수관내 미생물 재성장에 미치는 영향 - 우달식; 신성훈; 이호선; 황병기; 채수권 (한국수처리학회지, 21(2), 2013)
This study aims to measure the microorganisms attached in the steel pipe, stainless steel(STS 304), and PVC to find out the impact of the corrosion inhibitor on the microbial regrowth within the water pipe and at the same time compare the characteristics of biological film formation depending on the concentration of residual chlorine and the changes in the concentration of corrosion inhibitor. When the corrosion inhibitor was injected in the condition that the treatment water is more or less than TOC 2mg/L, the increase or decrease in the amount of attached microorganisms did not appear and the amount of attached microorganisms was less than the control group that the corrosion inhibitor was not injected. This means that phosphate components are not used as necessary nutrients for the growth of microorganisms in the condition that the concentration of organic matter is low and at the same time, is considered that the corrosion inhibitor formed the thin films on the surface of metal pipe to avoid the progression of corrosion, thus minimizing the growth environment where microorganisms like corrosion products are inhabitable. KCI Citation Count: 4